Evaluation of Expert System at Forensic Document Examinations in Turkey - Alkan, Nevzat; Sözen, Mehmet Şevki (The Bulletin of Legal Medicine, 1998)
Forensic document examination is one of the most important fields of Forensic Sciences. Purpose of our study is to analyse how. with whom and with which agencies and principles of expert applications related with forensic document examinations are made in our country. With this purpose, it is discussed by examining law paragraphs including expertise, legal expert organizations that work in this subject, forensic document examination laboratories occupied in these organizations, work responsibilities, technical and worker capacities and principles applied to choose their workers, private expert applications in forensic document examination and codes of The Society of Forensic Medicine Specialists and The Society of Forensic Sciences. The data we obtained showed that new legal arrengements are necessary for forensic document examinations in our country. In this way, certain work standards and educational rules will be formulated in application and sufficient controls will be ensured to avoid exploitation. Besides legal arrangements this will be possible with internal arrangements of the professional societies. Keywords: Forensic Medicine, Forensic Sciences. Forensic Document Examination, Graphology, Calligraphy